2000
DOI: 10.1006/bcmd.2000.0274
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Structure of the Human p47-phox (NCF1) Gene

Abstract: ABSTRACT:The cytosolic factor p47-phox, encoded by the NCF1 gene, is an essential component of the phagocyte NADPH-oxidase system. Upon activation of this multicomponent system, p47-phox translocates to the membrane and participates in the electron transfer from NADPH to molecular oxygen. A deficiency or absence of p47-phox is the most common autosomal form of chronic granulomatous disease (CGD). We have cloned and characterized the NCF1 gene from four bacteriophage clones, a P1 clone and genomic DNA from norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…2) was performed by Sanger sequencing according to [5]; reference for the sequence was retrieved from [20]. Primers were developed on NCF1-specific points in the introns of NCF1 to amplify only NCF1-and not pseudo-genespecific sequences (Suppl.…”
Section: Sequencingmentioning
confidence: 99%
“…2) was performed by Sanger sequencing according to [5]; reference for the sequence was retrieved from [20]. Primers were developed on NCF1-specific points in the introns of NCF1 to amplify only NCF1-and not pseudo-genespecific sequences (Suppl.…”
Section: Sequencingmentioning
confidence: 99%
“…Sequencing of exon 4 and exon 7 of NCF1 was performed by Sanger sequencing according to Roos et al ,6 and reference for the sequence was retrieved from Chanock et al 7. Segregating SNPs between NCF1 and its pseudogenes showed that the PCR was NCF1 gene specific.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence implicates interferon-b as a mediator of NAPDH-enhancing disease amelioration. 60 The human NCF1 gene has two pseudogene duplications, 61,62 and has proven difficult to study in humans.…”
Section: Using Congenic Strains To Identify Genes and Their Functionsmentioning
confidence: 99%